-25=a(x-3)+3

Simple and best practice solution for -25=a(x-3)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25=a(x-3)+3 equation:


Simplifying
-25 = a(x + -3) + 3

Reorder the terms:
-25 = a(-3 + x) + 3
-25 = (-3 * a + x * a) + 3
-25 = (-3a + ax) + 3

Reorder the terms:
-25 = 3 + -3a + ax

Solving
-25 = 3 + -3a + ax

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
-25 + 3a = 3 + -3a + 3a + ax

Combine like terms: -3a + 3a = 0
-25 + 3a = 3 + 0 + ax
-25 + 3a = 3 + ax

Add '-1ax' to each side of the equation.
-25 + 3a + -1ax = 3 + ax + -1ax

Combine like terms: ax + -1ax = 0
-25 + 3a + -1ax = 3 + 0
-25 + 3a + -1ax = 3

Add '25' to each side of the equation.
-25 + 3a + 25 + -1ax = 3 + 25

Reorder the terms:
-25 + 25 + 3a + -1ax = 3 + 25

Combine like terms: -25 + 25 = 0
0 + 3a + -1ax = 3 + 25
3a + -1ax = 3 + 25

Combine like terms: 3 + 25 = 28
3a + -1ax = 28

Reorder the terms:
-28 + 3a + -1ax = 28 + -28

Combine like terms: 28 + -28 = 0
-28 + 3a + -1ax = 0

The solution to this equation could not be determined.

See similar equations:

| 12-4x=3x^3-x^2 | | 8x-9x^3+1=0 | | .005x-.07=.02x+.0032 | | 18x^2+21x-49=0 | | 5=2+3s | | 5n+17=8(-8-3n)-6 | | 9-0.1k=9 | | 2-5v=-v+2(1+7v) | | x+5+2x= | | 12-7n=6-8n | | 3(2x+3)=2x+21 | | 59x-(21x+34)=0 | | 28-5n=3(5-8n)-6 | | 2x+15=2y-15 | | 5(x+4)+-4x=18-23 | | -9g-6g-4=-16-16g | | -4(x-4)-6=-7+2(4-2x) | | 3x*2+6x+4800=0 | | y=-16x^2+9x+30 | | -14z+2z-7=-20-11z | | 10t=7y+15 | | 3(1-2x)=7-5x | | (2x-5)+(2x-5)+(3x-25)+(5x+45)=360 | | -6x=-2(-4+7x) | | 2x+5=135 | | 2+6y=12+7y | | -6(4k-7)-4k=-5-3(7k-4) | | 105+Y=105 | | 6y+2=-y+32 | | -9-5x=-19 | | 2(b-21)=41-3(b-4) | | (3x-7y)(x+3y)= |

Equations solver categories